2020
DOI: 10.1038/s41467-020-15560-x
|View full text |Cite|
|
Sign up to set email alerts
|

Ancient genomes reveal social and genetic structure of Late Neolithic Switzerland

Abstract: Genetic studies of Neolithic and Bronze Age skeletons from Europe have provided evidence for strong population genetic changes at the beginning and the end of the Neolithic period. To further understand the implications of these in Southern Central Europe, we analyze 96 ancient genomes from Switzerland, Southern Germany, and the Alsace region in France, covering the Middle/Late Neolithic to Early Bronze Age. Similar to previously described genetic changes in other parts of Europe from the early 3rd millennium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 52 publications
5
60
0
2
Order By: Relevance
“…Haak et al (2015) also observed that the T allele increased in frequency only after the Yamnaya Steppe ancestry became ubiquitous in Central and Western Europe. Consistent with these findings, it was recently identified that the T allele is possessed by only one CWC individual from Sweden (Malmström et al, 2019), only one Final Neolithic individual from Switzerland (Furtwängler et al, 2020), and none of 16 CWC individuals from Poland (Witas et al, 2012;Linderholm et al, 2020), to mention a few. Using 230 ancient Eurasians, Mathieson et al (2015) found that the earliest appearance of the T allele is in a Central European Bell Beaker sample dated to between 2450 and 2140 BC, and the selective sweep dated to the last 4000 years (Burger et al, 2007;Gamba et al, 2014;Haber et al, 2016 for a review).…”
Section: Discussionmentioning
confidence: 67%
“…Haak et al (2015) also observed that the T allele increased in frequency only after the Yamnaya Steppe ancestry became ubiquitous in Central and Western Europe. Consistent with these findings, it was recently identified that the T allele is possessed by only one CWC individual from Sweden (Malmström et al, 2019), only one Final Neolithic individual from Switzerland (Furtwängler et al, 2020), and none of 16 CWC individuals from Poland (Witas et al, 2012;Linderholm et al, 2020), to mention a few. Using 230 ancient Eurasians, Mathieson et al (2015) found that the earliest appearance of the T allele is in a Central European Bell Beaker sample dated to between 2450 and 2140 BC, and the selective sweep dated to the last 4000 years (Burger et al, 2007;Gamba et al, 2014;Haber et al, 2016 for a review).…”
Section: Discussionmentioning
confidence: 67%
“…ros Damgaard et al, 2018;Mittnik et al, 2018;Fu et al, 2016;Schiffels et al, 2016;Narasimhan et al, 2019;Lipson et al, 2017;Olalde et al, 2018;Brace et al, 2019;González-Fortes et al, 2017;Furtwängler et al, 2020;Fernandes et al, 2018;Antonio et al, 2019;Sikora et al, 2017;Krzewińska et al, 2018;Margaryan et al, 2020;Mathieson et al, 2015;Schroeder et al, 2019), we compiled metric data for 167 individuals (Caffell & Holst, 2012;Tebelškis & Jankauskas, 2002;Alpaslan-Roodenberg, 2001;Dunwell, 2007;Andrews & Thompson, 2016;Köhler et al, 2017;Fokkens et al, 2017;Boroneant, 2010;Pardini, 1977;Frei et al, 2019;Kjellström, 2005;Cairns, 2015;Price et al, 2016;Szczepanek, 2013;Alciati, 1967;Massy, 2018;Malmström et al, 2019;Berthold et al, 2008;Kitti, 2008;Saag et al, 2020;Auerbach & Ruff, 2004;Auerbach, 2004;Schiffels et al, 2016;Rosenstock et al, 2019). We removed 28 sam...…”
Section: Data Collectionunclassified
“…In future, aDNA results might provide information about pathogens, which could have caused the death of some individuals. A further factor to consider while searching for the causes of death is that the dolmen was used for several generations, based on radiocarbon dating (Steuri et al, submitted) and aDNA analysis (Furtwängler et al, in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…The preservation and representation of the skeletal remains were not further evaluated due to overall fragmentation and taphonomic alterations. For further biochemical analyses, the right partes petrosae ( n = 23) were sampled for aDNA (Furtwängler et al, , in preparation), stable isotope analyses, and radiocarbon dating (Siebke et al, in preparation) to ensure a congruent dataset and to overcome the limitations of commingled remains.…”
Section: Methodsmentioning
confidence: 99%